Nanovoids in dense hydroxyapatite ceramics after electric field assisted sintering. (18th August 2018) - Yun, Jondo; Qin, Wei; van Benthem, Klaus; Thron, Andrew M.; Kim, Sukyoung; Han, Young-Hwan
ABSTRACT: Nanoporous hydroxyapatite (HA) ceramics were consolidated using conventional or free sintering, spark plasma sintering (SPS) and flash sintering (FS). Microstructures formed during electric field assisted sintering, which includes SPS and FS revealed that nanovoids were retained within HA grains during processing. After free sintering, however, no nanovoids were detected by transmission electron microscopy (TEM). The observed nanovoids were confirmed not induced by electron beam damaging, and showed either a round or faceted shape with diameters ranging between 5 and 10 nm. In-situ TEM heating experiments demonstrated that nanovoids remained stable up to 900°C but disappeared at a temperature as high as 1100°C.